Search for heavy particles decaying into top-quark pairs using lepton-plus-jets events in proton–proton collisions at $\sqrt{s} = 13$ $\text {TeV}$ with the ATLAS detector - ATLAS collaboration (2891 authors) (2019)
Submitted by Helmut Wolters (helmut@coimbra.lip.pt) on 2019-02-05T16:16:26Z No. of bitstreams: 2 1.pdf: 2049345 bytes, checksum: 9471dd74cff6d7057c050d627c8bdb18 (MD5) zip/1670803.zip: 1202820 bytes, checksum: d0db5fe5d65413370f9202f8329ad2a7 (MD5)